2015
DOI: 10.1186/s13058-015-0516-0
|View full text |Cite
|
Sign up to set email alerts
|

Markers for the identification of late breast cancer recurrence

Abstract: Postmenopausal women with early breast cancer are at an ongoing risk of relapse, even after successful surgery and treatment of the primary tumor. The treatment of breast cancer has changed in the past few years because of the discovery of prognostic and predictive biomarkers that allow individualized breast cancer treatment. However, it is still not clear how to identify women that are at high risk of a late recurrence. Clinical parameters are good prognostic markers for early recurrence, but only nodal statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 59 publications
(79 reference statements)
2
51
0
Order By: Relevance
“…We compared expression levels of ER and PgR and Ki67 LI in patients without recurrence among 4 groups defined by menopausal status and age ( Previous studies reported that tumor grade and Ki67 expression were predictive only of recurrence in the first 5 years after diagnosis [7,12]. The present study also indicated that tumor grade and/or Ki67 LI were predictors of early recurrence, but not of late recurrence in both pre-and postmenopausal women.…”
Section: Expression Levels Of Er and Pgr And Ki67 LI In Patients Witsupporting
confidence: 55%
See 1 more Smart Citation
“…We compared expression levels of ER and PgR and Ki67 LI in patients without recurrence among 4 groups defined by menopausal status and age ( Previous studies reported that tumor grade and Ki67 expression were predictive only of recurrence in the first 5 years after diagnosis [7,12]. The present study also indicated that tumor grade and/or Ki67 LI were predictors of early recurrence, but not of late recurrence in both pre-and postmenopausal women.…”
Section: Expression Levels Of Er and Pgr And Ki67 LI In Patients Witsupporting
confidence: 55%
“…Therefore, accurate and reliable estimates of the risk of recurrence after five years of endocrine therapy are necessary to enable appropriate decisions regarding extended endocrine therapy. It has been considered that the risk of long-term relapse is related to the number of positive lymph nodes and large size of invasive tumors [7]. Furthermore, multi-parameter molecular assays, including IHC4, OncotypeDX, EndoPredict, PAM50 and Breast Cancer Index, have been developed for predicting early and/or late distant recurrence [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and reliable estimates of the risk of recurrence after five years of endocrine therapy, which would enable appropriate decisions regarding extended periods of this treatment modality, are therefore required. The risk of long-term relapse is related to the number of positive lymph nodes and the large size of invasive tumors [7][8][9][10]. Furthermore, multi-parametric molecular assays, including IHC4, OncotypeDX, EndoPredict, PAM50, and Breast Cancer Index, have been developed for predicting early (relapse less than five years after initial treatment) and/or late distant recurrence [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the adjuvant therapy of ER-positive tumors, 5 years of treatment with anti-estrogens reduces the incidence of disease progression by about 50%, however, the disease progression can still occur after the therapy has been discontinued (Smith et al 2014, Sestak & Cuzick 2015, Goss et al 2016. Extending adjuvant treatments for additional 5 years efficiently reduces the incidence of late relapse but is associated with increased risk of adverse side effects of anti-estrogens (Davies et al 2013, Goss et al 2016, Sestak et al 2016.…”
Section: Androgen Excess As a Factor Of Risk Of Late Relapse And Of Rmentioning
confidence: 99%
“…Five years of adjuvant therapy significantly improve the outcomes of these patients compared to none therapy (Smith et al 2014, Sestak & Cuzick 2015, Sestak et al 2016, but, despite their effectiveness, adjuvant hormonal treatments encounter two major clinical problems: high rate of de novo or acquired resistance to anti-estrogens, that prevents about 50% of patients to benefit with the therapy (Rechoum et al 2014, Fuji et al 2014, Ciupek et al 2015 and occurrence of late relapse after anti-estrogens have been discontinued (Smith et al 2014, Sestak & Cuzick 2015, Sestak et al 2016.…”
Section: Introductionmentioning
confidence: 99%